Changes in the Microbiome in the Soil of an American Ginseng Continuous Plantation - Zhang, Jiguang; Fan, Sanhong; Qin, Jun; Dai, Jichen; Zhao, Fangjie; Gao, Liqiang; Lian, Xihong; Shang, Wenjing; Xu, Xiangming; Hu, Xiaoping (Frontiers in Plant Science, 2020)
American ginseng is an important herbal medicinal crop in China. In recent years, there is an increasing market demand for ginseng but the production area has been shrinking due to problems associated with continuous monocropping. We analyzed microbiome in the bulk soils to assess whether and, if so, what changes in the bulk soil microbiome are associated with continuous American ginseng cropping. The alpha diversity of fungi and bacteria was significantly lower in the soils planted with American ginseng than the virgin (non-planted) land. The relative abundance of Fusarium spp. and Ilyonectria spp., known plant root pathogens, was much higher in the soils cropped with American ginseng than the non-planted. On the other hand, a number of bacteria with biodegradation function, such as Methylibium spp., Sphingomonas spp., Variovorax spp., and Rubrivivax spp. had lower abundance in the soils cropped with American ginseng than the non-cropped. In addition, soil pH was lower in the field planted with American ginseng than the non-planted. Accumulation of fungal root pathogens and reduction of soil pH may therefore have contributed to the problems associated with continuous monocropping of American ginseng.